Pelatihan Digital Marketing dan Manajemen Keuangan untuk UMKM dan BUMDesa Wija Sari di Desa Samsam, Kabupaten Tabanan : Pengabdian - Made Edy Septian Santosa; Astiti, Ni Putu Yeni; Raharja, Made Agung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity was conducted in Samsam Village, Kerambitan District, Tabanan Regency, Bali, with a focus on management and digital marketing training for the Village-Owned Enterprise (BUMDesa) Wija Sari and a local Small and Medium-sized Enterprise (UMKM), Kue Cemilan Cantik Gekka. The goal was to enhance the professionalism of business management and expand their market reach. Based on initial observations, the BUMDesa and UMKM in Samsam Village faced challenges such as manual and unprofessional financial management and limited use of digital promotional media. BUMDesa Wija Sari only used a WhatsApp group for socialization and promotion, while the UMKM Kue Cemilan Cantik Gekka relied solely on word-of-mouth marketing.The methods used were training and mentoring. The training covered two main aspects: product marketing digitalization through social media and professional financial management. The results showed a significant increase in the knowledge and skills of the participants, the creation of social media accounts for the BUMDesa and UMKM, and changes in their financial reporting systems. However, challenges such as limited training time and varying levels of digital literacy among participants still existed. Therefore, the service team provided follow-up consultation sessions to ensure the sustainable implementation of the strategies.